Surgical management of giant scrotal lymphedema in morbidly obese patient with trisomy 21 - Yasser M. Elkiran, PhD; Amr M. Elshafei, PhD; Mohammed S. Abdelgawwad, PhD; Mohammed A. Abdelmaksoud, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2019)
Huge scrotal lymphedema is a rare problem that affects the patient's lifestyle and leads to physical and emotional disability. It also carries potential challenges for the treating surgeon, especially if the patient is noncompliant or morbidly obese. A 21-year-old morbidly obese trisomy 21 man with huge scrotal lymphedema and buried penis that developed within 2 years presented for excision scrotoplasty with reconstruction of the penis using the original invaginated penile skin. Giant scrotal lymphedema with buried penis can be treated successfully by excision scrotoplasty with preservation of the invaginated healthy penile skin to reconstruct the penis. Keywords: Lymphedema, Genitalia, Trisomy, Scrotoplasty